An extracellular protease containing a novel C-terminal extension produced by a marine-originated haloarchaeon - Han, Dong; Hou, Jing; Cui, Heng-Lin (Frontiers in Marine Science, 2023)
Marine microorganisms have long been acknowledged as a significant reservoir of enzymes required for industrial use. In this study, a novel extracellular protease HslHlyB derived from marine-originated haloarchaeon Halostella pelagica DL-M4T was identified. HslHlyB contained polycystic kidney disease (PKD) domain and pre-peptidase C-terminal (PPC) domain at the C-terminus. Truncation and replacement of the C-terminal extension (CTE) of HslHlyB demonstrated the importance of the CTE in maintaining the protease activity secreted by haloarchaeon and confirmed the substitutability of the CTE between extracellular proteases from haloarchaea (halolysins). HslHlyB and HslHlyBΔCTE were expressed in Escherichia coli BL21(DE3), and purified by high-affinity column refolding and gel filtration chromatography. The molecular masses of HslHlyB and HslHlyBΔCTE were 42 kDa and 20 kDa, respectively. The optimum catalytic reaction conditions were 50 C, pH 8.5, NaCl 3.5 M and 50 C, pH 7.5, NaCl 3 M, respectively. They showed good stability and hydrolysis capabilities towards a wide range of protein substrates. HslHlyBΔCTE showed higher catalytic reaction rate and better thermal stability than the wild type against azocasein and Suc-AAPF-pNA. The hydrolysates of soybean protein hydrolyzed by HslHlyBΔCTE had smaller average molecular masses and shorter average peptide chain lengths than those by HslHlyB. These results indicated the diversity of halolysins from marine-originated haloarchaea to harness scarce organic nitrogen in the marine environment.